Desenvolvimento de objetos de aprendizagem para a aprendizagem baseada em problemas no ensino de computação para engenharias - Silva, Narci Nogueira da (2017)
Context: Considering the teaching computation to engineering, problem-based learning (PBL) is a successful approach. However, it is not trivial to create and disseminate educational resources that support PBL activities. Learning Objects (LOs) can address these issues. Objevtive: This work aims to add to the LODM, a method of developing LO based on conceptual, instructional and interaction models, a new profile with elements characteristic of PBL. Using the mechanism that allows the extension of new profiles to the LODM, we have created the LODM+PBL. Considering this new method, we still create LOs and execute two studies in initial classes of Engineering courses, focusing on computer programming. Method: The new method consisted of the analysis of PBL activities; definition of modeling elements for PBL and its UML structure; development and evaluation of LO. The creation process was based on the Analysis, Design, Development, Implementation and Evaluation – ADDIE. Results: Analyzing the reports, final products and artifacts generated and a questionnaire applied at the end of tne PBL activities, we evaluated the quality of LO considering two perspectives: studentss perception and motivation; and the achievement of learning objectives. The results suggest that the LODM+PBL can be applied successfully to the creation of Los with PBL elements for the concepts of Engineering for Computing. Conclusions: Analyzing the development of OAs, it was observed that the method satisfactorily assisted in the understanding of the characteristics and requirements of PBL for creating and application of LOs. Still, the two studies have produced artifacts that evidence that the improved LODM model and the PBL methodology to stimulate and improve the understanding of the proposed educational objectives.